“A melancholy country called Scotland”: assimilazione culturale e resistenza nel contesto della strutturazione della Britishness (Altre Modernità, 2022)
After the promulgation of the Union Act (1707), England had to face with the existence of another distinct socio-cultural identity. It was possible to made Scotland part of Great Britain, where the predominant ideology was the English one?Nowadays, the assimilation or non-assimilation of the Scottishness in the context of an Anglo-Britishness culture is an historiographical topic still in course of discussion. The aim of this paper will be to examine the English perception of Scotland through the Londoners periodic paper and to summarize the main historiographic interpretation of the assimilation of Scotland in the new-born British Empire. Moreover, it will be illustrated the strong correlation between the Scottishness and the periodic press in the mid-18th century, highlighting how the question of the Scottish assimilation was a cultural issue instead of a political one and, secondly, how it was explored by the articles of the Universal Magazine. For this reason, four short articles, published by the Universal’s editorial board between 1747 and 1778, will be analysed. Two conclusions are consequential of this reflection: on the one hand, it will be illustrated that in the Universal Magazine a way of thinking that was typically scotophobic coexisted with one another that had the tendency to defend the cultural alterity of Scotland. On the other hand, the cultural assimilation of Scotland will be described as a complex and uncertain process, in the context of the establishment of the Anglo-British culture in the mid-18th century.
Keywords: britishness; scottishness; Universal Magazine; scotophobia; history of British periodical press